Numerical Analysis of the Influence of Prestressed Steel Wires on Vehicle-Bridge Coupling Vibration of Simply Supported Beams on High-Speed Railway - Daihai Chen; Yanchang Wan; Shizhan Xu; Zheng Li; Yilin Fang (The Baltic Journal of Road and Bridge Engineering, 2022)
By the theory of vehicle-bridge coupled vibration analysis in railways, the dynamic analysis model for space of the train-track-bridge-steel wires coupled system was established. Moreover, a corresponding program was compiled based on the train-track-bridge-steel wires coupling vibration analysis method. Taking a 32 m simple beam which is in high-speed railways as the subject of study, the influence of effective prestress, steel wires eccentricity and vehicle speed on the dynamic response of the vehicle-bridge coupled vibration was analysed. The results show that the bridge dynamic response is remarkably influenced by prestressed steel wires. With the prestress increasing, the crest of the vertical dynamic response at the midspan decreased first, then increased. Moreover, the minimum peak value appeared when the prestress was 1300 MPa. When the steel wires were deflected downward relative to the design position, the vertical displacement of the bridge decreased by more than when the downshift occurred. The extreme values of the bridge lateral dynamic response and the train body acceleration response appeared when the train ran at 300 km/h. Prestressed steel wires had little effect on the dynamic response in the transverse direction of the bridge and train body.